Production of Biopharmaceuticals in Nicotiana benthamiana—Axillary Stem Growth as a Key Determinant of Total Protein Yield - Goulet, Marie-Claire; Gaudreau, Linda; Gagné, Marielle; Maltais, Anne-Marie; Laliberté, Ann-Catherine; Éthier, Gilbert; Bechtold, Nicole; Martel, Michèle; D’Aoust, Marc-André; Gosselin, André; Pepin, Steeve; Michaud, Dominique (Frontiers in Plant Science, 2019)
Data are scarce about the influence of basic cultural conditions on growth patterns and overall performance of plants used as heterologous production hosts for protein pharmaceuticals. Higher plants are complex organisms with young, mature and senescing organs that show distinct metabolic backgrounds and differ in their ability to sustain foreign protein expression and accumulation. Here, we used the transient protein expression host Nicotiana benthamiana as a model to map the accumulation profile of influenza virus hemagglutinin H1, a clinically promising vaccine antigen, at the whole plant scale. Greenhouse-grown plants submitted to different light regimes, submitted to apical bud pruning or treated with the axillary growth-promoting cytokinin 6-benzylaminopurine were vacuum-infiltrated with agrobacteria harboring a DNA sequence for H1 and allowed to express the viral antigen for 7 d in growth chamber under similar environmental conditions. Our data highlight the importance of young leaves on H1 yield per plant, unlike older leaves which account for a significant part of the plant biomass but contribute little to total antigen titer. Our data also highlight the key contribution of axillary stem leaves, which contribute more than 50% of total yield under certain conditions despite representing only one third of the total biomass. These findings underline the relevance of both considering main stem leaves and axillary stem leaves while modelling heterologous protein production in N. benthamiana. They also demonstrate the potential of exogenous applied growth-promoting hormones to modulate host plant architecture for improvement of protein yields.